Contributions to Iraqi Children Press in Promoting Educational Values in Children - ذويب عثمان محمد (ALBAHITH ALALAMI, 2017)
The researcher aims at focusing on the participations of children journalism in supplying the educational values for them. The researcher uses the survey method in addition to the method of content analysis through analyzing the content of two journals (Majalati and The Mezmar). Both of them deal with children issues. The researcher concludes that the two journals focus on literary arts in a way which surpasses the journalistic arts. Furthermore, the two journals have concerned with showing the positive values as well as insuring the necessity of rectifying the wrong behaviors. Finally, the researcher recommends that it is necessary to improve the employees who work with children journals through training, workshops, which will enable them acquiring the necessary skills.